Pengetahuan Pilot Drone Mengenai Aspek K4L Pada Penggunaan Drone Di Bidang Teknik Sipil - Alghifari, Muhammad; Aini, Suci Qurratul; sari, Hasrina (Yayasan Cendekia Gagayunan Indonesia, 2025)
The use of drones in various sectors is growing rapidly. Drone technology contributes various benefits such as operational efficiency, cost reduction, and the ability to reach hard-to-reach areas. However, the use of drones also brings its own challenges related to occupational safety, health and security aspects and their impact on the environment. Occupational and Environmental Safety, Health and Security (K4L) is a series of activities or efforts to realize occupational and environmental safety, health and security (K4L). K4L issues in drone use can be caused by technical problems with drones, such as mechanical and electrical component failures, as well as software and flight control system malfunctions, playing a major role in drone accidents in the workplace. Another factor is human factors, such as inadequate organizational training for drone operators, overconfident pilots, high workload, and inattention, can cause drone accidents. One of the uses of drones is in the field of civil engineering. This research is a descriptive study using a questionnaire with research respondents, namely 10 drone pilots in Civil Engineering. The results showed good knowledge of drone pilots regarding the k4L aspects of drone use in the Civil Engineering Field with a score of 9.5 out of 10 or 95%.